Real estate prices and the importance of bequest taxation - Giorgio Bellettini; Filippo Taddei (Center for Economic Studies and ifo Institute (CESifo), 2009)
Taxation of bequests and donations is an important determinant of real estate prices. We show that, ceteris paribus, a decrease in taxes on inter vivos donations and bequests brings about an increase in real estate prices. We provide a general equilibrium rationalization in the context of OLG economies featuring intergenerational altruism. This has relevant policy implications. We test the predictions of our theory employing a unique policy shock: the abolition of bequest and donation taxation that took place in Italy in 2001. Considering this policy shift provides the first evidence that a drastic reduction in bequest and donation taxation significantly increased real estate prices. Our estimates suggest that the 2001 abolition of taxation on bequests and donations alone led to an appreciation of residential real estate in excess of 10%.
Keywords: E62; H30; 330; Real estate prices; donations; bequest taxation; Immobilienpreis; Erbschaftsteuer; Steuerwirkung; Overlapping Generations; Privater Transfer; Allgemeines Gleichgewicht; Theorie; Italien